Fabrication of Au(Ag)/AgCl/Fe3O4@PDA@Au nanocomposites with enhanced visible-light-driven photocatalytic activity. Issue 39 (18th September 2015) - Wang, Baoyu; Zhang, Min; Li, Weizhen; Wang, Linlin; Zheng, Jing; Gan, Wenjun; Xu, Jingli
Abstract : A novel Au(Ag)/AgCl/Fe3 O4 @Pdop@Au multifunctional nanotube was obtained, which showed obvious near-infrared absorption and exhibited excellent photocatalytic via visible light. Abstract : Here we reported a facile method to synthesize multifunctional nanocables with a tunable chemical composition. Through the in situ templating method, polydopamine could be directly coated onto the magnetic silver nanowires to form Ag NW/Fe3 O4 @PDA nanocables. Then, Au(Ag)/AgCl/Fe3 O4 @PDA@Au was elaborately fabricated by utilizing Ag NWs/Fe3 O4 @PDA as a template by means of spatially confined galvanic replacement and reduction among Ag NWs, PDA and HAuCl4 . These multifunctional nanotubes exhibited excellent photocatalytic activity in the presence of visible light.